Consequences of the Loss of the Leased Asset for the Parties to the Leasing Agreement - D. A. Filimonov (Сибирское юридическое обозрение, 2015)
The article reveals the practical consequences resulting from the loss of the object of lease concerning allocation of the risk of loss between the parties of redemption leasing. The author makes the conclusion that the terms of the leasing subject insurance in the lease agreement should be considered as a circumstance excluding the grounds for adverse consequences of an insured event of the parties to the lease agreement. It is therefore proposed to consider the norms of Article 26 of the Law on Leasing in connection with the rules of Article 21 of this law. Ключевые слова: лизинг, риск, страховой случай, лизинговый платеж. Leasing, risk, insured event, lease payment.